Micro Vascular Changes in the Placenta of Bangladeshi Overt Diabetic Mothers and Hypertensive Diabetic Mothers - Rahman, H; Khalil, M; Ferdousi, R; Uddin, M; Chowdhury, MM; Sultana, SZ; Mannan, S (Journal of Bangladesh Society of Physiologist, 2008)
It is a significant medical problem when Pregnancy is complicated by diabetes and/or hypertension which affect not only affecting maternal health, but also jeopardizing fetal normalcy? The placenta being the bridge between maternal fetal activities, this structure is considered as a window through which understanding of maternal dysfunctions as well as of their impacts on fetal wellbeing can be obtained. And as it is an almost all-vessel organ, its functional status depends primarily on the structural status of its vessels. To observe vascular changes in the placenta, a study was carried out on 44 placentas.19 from overt diabetic mothers having no hypertension and 5 from hypertensive diabetic mothers, and 20 from control group having no hypertension or diabetes. These were collected just after delivery though caesarian section. Microscopic findings of the study were that there was a trend of greater intimal thickness at the second branching site in the overt diabetes group than the control group. But at the first and last branching site this tendency was reversed. But none of these tendencies reached statistical significance. In case of the hypertensive diabetes group, there was a tendency of greater intimal thickness at the first, second and last branching sites as compared to the control group. Hypertensive diabetes group also showed significantly greater intimal thickness at first and last branching sites than the overt diabetes group. Key words: Placenta, diabetes, blood vessels, hypertensionJ Bangladesh Soc Physiol. 2006 Dec;(1):27-34